2021
DOI: 10.7150/ijms.61309
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of the molecular mechanisms in idiopathic pulmonary fibrosis

Abstract: Rationale: Idiopathic pulmonary fibrosis (IPF) is one of the most aggressive forms of idiopathic interstitial pneumonia. Some miRNAs may be associated with IPF and may affect the occurrence and development of IPF in various pathways. Many miRNAs and genes that may be involved in the development of IPF have been discovered using chip and high throughput technologies. Methods: We analyzed one miRNA and four mRNA databases. We identified hub genes and pathways related to IPF using GO, KEGG enrichment analysis, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…For instance, AGER , SPP1 , MMP7 and CRLF1 are included in a review list of transcriptionally deregulated genes during IPF compiled by [34] . In addition, genes such as COL1A1 , COL15A1 , COMP , MMP7 and LCN2 were identified as potential IPF drivers by previous exploratory research deliverables comparing the transcriptomes of IPF patients to those of control individuals ( Table 2 ) [35] , [36] , [37] , [38] , [39] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, AGER , SPP1 , MMP7 and CRLF1 are included in a review list of transcriptionally deregulated genes during IPF compiled by [34] . In addition, genes such as COL1A1 , COL15A1 , COMP , MMP7 and LCN2 were identified as potential IPF drivers by previous exploratory research deliverables comparing the transcriptomes of IPF patients to those of control individuals ( Table 2 ) [35] , [36] , [37] , [38] , [39] .…”
Section: Resultsmentioning
confidence: 99%
“…3 B), all three strategies seem to have comparable performance as they share 65% of the 1st quartile of the features list. More than half of these common features (8/13) are among the text mining highlighted ones, while four ( COMP , COL1A1 , COL17A1 and COL5A2 ) have been proposed as biomarkers in the past [35] , [36] , [38] , [39] . In addition, comparison of the lists along their whole length using Kendall ranking correlation, revealed strong similarities of BIRRA with each of the SHAP-weighted majority voting and MAIC methods, while the latter two share less common rankings ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lamas et al found that the median delay from the onset of clinical symptoms to the first in-hospital diagnosis was approximately 2.2 years, which was associated with a higher rate of death from IPF (P = 0.03) [21] . In the past few years, an increasing number of studies have focused on the cellular and molecular mechanisms of IPF, and progress has been made [22] . Several blood proteins, such as metalloproteases-7 (MMP7), SP-A, and SP-D, can help distinguish IPF from other ILDs, even if they are not included in the guidelines [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to further verify miRNA conservation between species, sequence analysis was performed and showed that the sequences of miR-125a-3p and miR-199a-5p in mice were identical to those in humans. Strikingly, in patients with IPF, upregulated miR-199a-5p regulated Vegfa and led to the development of IPF or other fibrosis-related diseases ( Zhu et al, 2021 ). Of course, we noticed that many hub genes have no significance in human samples, which may be caused by the differences between species.…”
Section: Discussionmentioning
confidence: 99%